The Ohel of Israel Joshua Trunk in the Jewish Cemetery in Kutno (Poland) - Artur Ginter; Judyta Ginter (Fasciculi Archaeologiae Historicae)
In 2020, the Agudat Israel Organisation and the Jewish Religious Community in Łódź came up with an idea to commemorate the once-venerated grave of Israel Joshua Trunk by rebuilding the ohel that had been erected over it. The deceased was one of the most famous rabbis of his time and a commonly known wise man honoured with the title of gaon. In order to implement this idea archaeological excavations began in the Jewish cemetery in Kutno with the aim to find the foundations of the building destroyed during the Second World War and to draw up documentation that would allow it to be rebuilt. The research goals were achieved and the lost ohel was uncovered along with its accompanying buildings, which most likely consisted of a 20th-century tomb of another person and the foundations of a large obelisk and tombstone.